Single-component nanodiscs via the thermal folding of amphiphilic graft copolymers with the adjusted flexibility of the main chain. Issue 18 (19th April 2022) - Nishimura, Tomoki; Hatatani, Yusuke; Ando, Mitsuru; Sasaki, Yoshihiro; Akiyoshi, Kazunari
Abstract : A strategy for the fabrication of nanodiscs via the self-assembly of thermoresponsive amphiphilic graft copolymers is demonstrated. Abstract : Nanodiscs have attracted considerable attention as structural scaffolds for membrane-protein research and as biomaterials in e.g. drug-delivery systems. However, conventional disc-fabrication methods are usually laborious, and disc fabrication via the self-assembly of amphiphiles is difficult. Herein, we report the formation of polymer nanodiscs based on the self-assembly of amphiphilic graft copolymers by adjusting the persistence length of the main chain. Amphiphilic graft copolymers with a series of different main-chain persistence lengths were prepared and these formed, depending on the persistence length, either rods, discs, or vesicles. Notably, polymer nanodiscs were formed upon heating a chilled polymer solution without the need for any additives, and the thus obtained nanodiscs were used to solubilize a membrane protein during cell-free protein synthesis. Given the simplicity of this disc-fabrication method and the ability of these discs to solubilize membrane proteins, this study considerably expands the fundamental and practical scope of graft-copolymer nanodiscs and demonstrates their utility as tools for studying the structure and function of membrane proteins.